INTERNATIONAL ROAD CARGO TRANSPORT IN POLAND AND OTHER EU COUNTRIES - Elżbieta MACIOSZEK; Agata KUREK (Scientific Journal of Silesian University of Technology. Series Transport)
In the modern world, transport as an integral part of social life is important. The development of all modes of transport requires continuous efficient management of the transport process, as well as the use of tools to optimise this process. This article aims to analyse international road cargo transport in EU countries and Poland from 2008-2018. The first part of this article analyses the number of employees and the trade of transport companies in EU countries. Then, the share of individual modes of transport in the transport of cargo in Poland from 2008 and 2018 is presented. The next section presents the results of the forecast of the volume of cargo transported by road in Poland from 2019-2021. The forecast values of the volume of cargo transport in Poland for 2019-2021, which were determined from the additive and multiplicative model, are at a similar level to the values for 2008-2018.